Unraveling the impact of customer mistreatment on highway toll collectors’ turnover intentions: the roles of stress symptoms, affective commitment, and neuroticism - Gao, Yongduan; Liu, Yanyan; He, Jianhua; Zhou, Jiaxin (Frontiers in Psychology, 2024)
In the service industry, highway toll collectors serve as a distinctive frontline workforce who frequently encounter mistreatment from customers. Unfortunately, these behaviors have not received the attention and resolution they deserve, resulting in significant physical and psychological stress for toll collectors and exacerbating turnover rates. The study highlights how customer mistreatment affects toll collectors' turnover intentions by performing the sequential mediating roles of stress symptoms and affective commitment and assumes that neuroticism exacerbates the stress symptoms resulting from customer mistreatment based on affective events theory. The model was tested using data collected from 230 highway toll collectors in Zhuhai, China. All hypotheses received support. This study holds both theoretical and practical implications for future research.